Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4184/asj.2014.8.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts of Anterior Cervical Discectomy and Fusion: A Review of Literature

Abstract: Anterior cervical discectomy and fusion (ACDF) is a safe and effective procedure for degenerative cervical spinal disease unresponsive to conservative management and its outstanding results have been reported. To increase fusion rates and decrease complications, numerous graft materials, cage, anterior plating and total disc replacement have been developed, and better results were reported from those, but still there are areas that have not been established. Therefore, we are going to analyze the treatment out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 71 publications
0
51
0
Order By: Relevance
“…10,21 However, both physicians and hospital systems have expressed concern about the impact of obesity on the outcomes and costs of spinal procedures. Previous studies have demonstrated that obesity is associated with longer operative times and increased blood loss during spinal surgery.…”
mentioning
confidence: 99%
“…10,21 However, both physicians and hospital systems have expressed concern about the impact of obesity on the outcomes and costs of spinal procedures. Previous studies have demonstrated that obesity is associated with longer operative times and increased blood loss during spinal surgery.…”
mentioning
confidence: 99%
“…Cage with bone grafts is good to sustain axial loading and the locking plates in addition to preventing rotation provides good load sharing device. 9 In our series, out of 3 cases with burst fractures neurological deficit was improved to normal only in one case.…”
Section: Discussionmentioning
confidence: 88%
“…This procedure generally provides good clinical results and high patient satisfaction scores [1]. Postoperative dysphagia is a common consequence of an anterior exposure following ACDF, and can occur in up to 71% of patients in the early postoperative period [2].…”
Section: Introductionmentioning
confidence: 99%